Sequential combination chemotherapy in human breast cancer: a basis for increased antineoplastic activity and bone marrow protection - Davis, J.H.; Desoto, J.A.; Fryar, E.B.; Southerland, W.M.; Bowen, D. (Cellular and Molecular Biology, 2007)
These studies were designed to develop procedures that would capitalize on the growth inhibitory effects of tamoxifen (Tam) and methotrexate (MTX) in breast cancer, while protecting bone marrow with a priming dose of 5-fluorouracil (5-FU). High-dose MTX (10 Î¼M) cytotoxicity is maintained in MCF-7 breast cancer cells but reduced in human bone marrow by a priming and nontoxic dose of 5-FU (10 Î¼M). MTX cytotoxicity is decreased in MCF-7 breast cancer cells when the selective estrogen receptor modulator (SERM) Tam (10 Î¼M) is administered 24 hours prior to 5-FU (10 Î¼M) followed two hours later by MTX (early Tam) resulting in a growth rate of 57.42 ± 4.38% of the control rate. However, when breast cancer cells are exposed to Tam 24 hours after 5-FU + MTX (late Tam), the interaction between MTX and Tam is not antagonistic, the percentage of the control is 29.47 ± 4.54%. Bone marrow exposure to these drug combinations exhibits a protective effect to the MTX cytotoxicity, with the early Tam combination yielding 59.45 ± 16.38% of the control for MTX alone. These studies suggest that a) Tam in combination with a priming dose of 5-FU protects bone marrow from MTX cytotoxicity, b) the interactions between Tam and MTX are sequence-dependent, c) Tam decreases the effect of MTX when Tam administration precedes MTX.